2020
DOI: 10.3390/biom10040536
|View full text |Cite
|
Sign up to set email alerts
|

Bacopa monnieri and Their Bioactive Compounds Inferred Multi-Target Treatment Strategy for Neurological Diseases: A Cheminformatics and System Pharmacology Approach

Abstract: Neurological diseases (NDs), especially Alzheimer’s and Spinocerebellar ataxia (SCA), can severely cause biochemical abnormalities in the brain, spinal cord and other nerves of human beings. Their ever-increasing prevalence has led to a demand for new drug development. Indian traditional and Ayurvedic medicine used to combat the complex diseases from a holistic and integrative point of view has shown efficiency and effectiveness in the treatment of NDs. Bacopa monnieri is a potent Indian medicinal herb used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 17 publications
0
55
0
4
Order By: Relevance
“…The unavailability and ineffectiveness of anti-COVID-19 medicines to deal with this noxious infection make it an urgent need to identify the novel drugs/compounds that are efficacious in the control and treatment of this deadly infection. The effectiveness of traditional Indian medicines was well known for over 1000 years of practice [ 31 ]. Despite the fact that the pharmaceutical ingredients of medicinal plants have been extorted and purified for unsullied drug development, this method still ends up in failure due to the higher violation of chemical components and functional drug regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unavailability and ineffectiveness of anti-COVID-19 medicines to deal with this noxious infection make it an urgent need to identify the novel drugs/compounds that are efficacious in the control and treatment of this deadly infection. The effectiveness of traditional Indian medicines was well known for over 1000 years of practice [ 31 ]. Despite the fact that the pharmaceutical ingredients of medicinal plants have been extorted and purified for unsullied drug development, this method still ends up in failure due to the higher violation of chemical components and functional drug regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be also seen as a major complexity and is confronting another complexity, which essentially throw more light in the understanding of the entire human physiological system by controlling the molecular cross-talk between all the immunological key elements within the species. On the other hand, the exact mechanism of the immune responsive targets and biological pathways of herbal medicines remains poorly understood [ 31 ]. Hence, in this pilot study, we employed immuno-transcriptomics, cheminformatics, interactomics and integrated pharmacology strategy for the first time to unravel the COVID-19 immune targets and their associated signaling pathways, pharmacological roles of J. adhatoda, O. sanctum, S. trilobatum, A. paniculata, Eucalyptus Sp., A. officinarum and P. amboinicus derived bioactive compounds in the treatment of COVID-19 at molecular system level.…”
Section: Discussionmentioning
confidence: 99%
“…Експериментальним підґрунтям мережевого підходу є дані про взаємозв'язки й конвергенцію різних патологічних метаболічних шляхів, які ведуть до атрофії і нейродегенерації. Відповідно, ефекти впливу на різні патогенетичні мішені можуть додаватися, множитися, але в будь-якому разі очікується їх синергія [3,5,6].…”
Section: практикуючому неврологу /To Practicing Neurologist/unclassified
“…[7]. Фітохімічними дослідженнями визначено, що до складу екстракту бакопи входить понад 50 біологічно активних речовин, зокрема алкалоїди, сапоніни, стероли, глікозиди, амінокислоти [5,7,8]. Фракція тритерпенових сапонінів у спеціалізованій літературі, що позначається узагальненим терміном «бакозиди», поділяється на субфракції А і В. Пізніше з екстракту була виділена й описана ще одна фракція сапонінів з ноотропними властивостями -бакопазиди I-XII [8].…”
Section: експериментальні передумовиunclassified
“…Jeyasri et al used a system pharmacology approach to develop a strategy for multi-target treatment based on traditional Ayurvedic medicine, Bacopa monnieri , for neurological diseases, focusing on Alzheimer’s disease (AD) and Spinocerebellar ataxia (SCA) [ 5 ]. When compared with commercially available drugs, it was revealed that the constituents of Bacopa monnieri have asiatic acid and loliolide for treating AD and SCA.…”
Section: Mechanistic Insights Into Bioactivitiesmentioning
confidence: 99%